Vodní měkkýši Svitávky v severních Čechách - Luboš Beran (Malacologica Bohemoslovaca, 2018)
Nine species of aquatic molluscs (four gastropods and five bivalves) were found at seven sites on the Svitávka River (a tributary of the Ploučnice River, Northern Bohemia). A small viable population of the endangered River pea mussel (Pisidium amnicum) was confirmed by its records at four sites and the critically endangered Fine-lined pea mussel (Pisidium tenuilineatum) was found at one site.